KRAS mutation analysis in genomic DNA isolated from formalin-fixed paraffin-embedded ovarian tissue: evaluation of a strip-based reverse-hybridisation assay. Issue 3 (22nd January 2011) - Kriegshäuser, Gernot; Auner, Veronika; Schuster, Eva; Holzer, Barbara; Oberkanins, Christian; Horvat, Reinhard; Speiser, Paul; Zeillinger, Robert
Abstract : Aims: To evaluate a reverse-hybridisation assay (strip assay) designed for the sensitive detection of 10 mutations in codons 12 and 13 of the KRAS gene. The strip assay relies on mutant-enriched PCR followed by reverse-hybridisation of biotinylated amplification products to oligonucleotide probes immobilised as an array of parallel lines on nitrocellulose test strips. Methods: The strip assay was used to analyse genomic DNA isolated from 120 formalin-fixed paraffin-embedded (FFPE) ovarian tissue samples. The samples were analysed in parallel using a biochip-based protocol (biochip assay) covering the same mutation spectrum, and results were compared with respect to sensitivity, specificity and operational input. Results: The strip assay identified 19 (16%) of 120 FFPE samples to carry a KRAS mutation; results were in agreement with those obtained by biochip hybridisation. Both assays had an analytical sensitivity of 1% when performed on FFPE-extracted DNA with approximately the same operational input needed for post-PCR processing. In contrast to the biochip assay, strip assay hybridisation may be automated to a large extent. Conclusions: The strip assay is an accurate and sensitive tool for the low to medium throughput detection of KRAS mutation in genomic DNA isolated from FFPE tissue.